The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12889-019-7283-2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges with seeking HIV care services: perspectives of older adults infected with HIV in western Kenya

Abstract: Background: While younger adults (15-49 years) form the majority of the population living with HIV, older adults (≥50 years) infected with HIV face multiple challenges related to the aging process and HIV. We explored the experiences of older persons infected with HIV at the Academic Model Providing Access to Healthcare (AMPATH) program in western Kenya to understand the challenges faced when seeking HIV care services. Methods: Between November 2016 and April 2017, a total of 57 adults aged 50 years and above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…We found that as people's health improved on ART, some individuals moved to places far from their ART refill clinics in pursuit of work to earn an income that resulted in missed ART refill appointments. The missed ART refill appointments could be due to either busy work schedules, or lack of transport fares, as described by other studies; 21,22 and strongly suggested that committed and well-supported biological caregivers are a key determinant to ART adherence as these experienced a stronger connotation to promote adherence. 23 Medication-related factors indicated that children who were instantly started on ART after diagnosis were twice more likely to adhere than those started later.…”
Section: Discussionmentioning
confidence: 80%
“…We found that as people's health improved on ART, some individuals moved to places far from their ART refill clinics in pursuit of work to earn an income that resulted in missed ART refill appointments. The missed ART refill appointments could be due to either busy work schedules, or lack of transport fares, as described by other studies; 21,22 and strongly suggested that committed and well-supported biological caregivers are a key determinant to ART adherence as these experienced a stronger connotation to promote adherence. 23 Medication-related factors indicated that children who were instantly started on ART after diagnosis were twice more likely to adhere than those started later.…”
Section: Discussionmentioning
confidence: 80%
“…Targeted HIV care for older adults would, therefore, significantly improve their access to and experience of HIV care. 22 According to this study, alcohol drinking is 2.3 times more a risk factor for HIV infection [OR= 2.302; 95% CI (1.4502,3.6499)] than do not drink as it increases sexual drive and leads unprotective sexual practices. The use of alcohol is believed to alter one's moods or emotional state either through the sustained release or inhibition of neurotransmitters, thereby enhancing or dampening the response of the individual.…”
Section: Dovepressmentioning
confidence: 76%
“…Updated findings . New studies offered further examples that confirmed the significance of competing priorities [ 38 , 39 , 41 , 61 , 67 , 71 , 72 , 80 , 89 ] and unpredictable life events [ 15 , 53 , 66 ]. Priorities include going to school and writing exams, seeking care for other chronic diseases such as diabetes of hypertension, and meeting religious obligations.…”
Section: Resultsmentioning
confidence: 99%
“…We extended this theme to include older people living with HIV [ 13 , 39 , 67 ]. Many older people feel insecure, outnumbered and considered already dead.…”
Section: Resultsmentioning
confidence: 99%